2015
DOI: 10.1161/strokeaha.115.010840
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Good Outcome After Stent-Retriever Thrombectomy in Acute Basilar Artery Occlusion

Abstract: Background and Purpose— Factors related to prognosis after a modern mechanical thrombectomy in patients with acute basilar artery occlusion remain unclear. This study investigated the prognostic factors for patients with acute basilar artery occlusion who underwent a stent-retriever thrombectomy. Methods— We analyzed clinical and pretreatment diffusion-weighted imaging (DWI) data in 50 consecutive patients with acute basilar artery occlusion treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 16 publications
8
79
6
Order By: Relevance
“…Procedural time is attributed to the reduction of the OTR. In our study, the mean procedural time was 39 (median 25) min, which is shorter than that in other studies [5,6,8,9,31,32.] This was also shorter than the mean procedural time of 48 min of BAO for anterior circulation at our facility.…”
Section: Discussioncontrasting
confidence: 63%
“…Procedural time is attributed to the reduction of the OTR. In our study, the mean procedural time was 39 (median 25) min, which is shorter than that in other studies [5,6,8,9,31,32.] This was also shorter than the mean procedural time of 48 min of BAO for anterior circulation at our facility.…”
Section: Discussioncontrasting
confidence: 63%
“…The previously identified factors independently associated with a good outcome after endovascular therapy in posterior circulation stroke included a low baseline NIHSS, successful reperfusion, a history of smoking, a high DWI‐Acute Stroke Program Early CT Score (ASPECTS), a shorter time to the start of procedure, a shorter time to reperfusion, better collateral status, and magnetic resonance imaging–based patient selection 3, 7, 9, 18, 19. Recently, Gory et al reported that only the failure to achieve successful reperfusion was an independent predictor of mortality at 3 months, in patients with acute BAO who underwent thrombectomy 20.…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate observed here could be explained by the delayed observed reperfusion times, a well-known factor for worse prognosis [21]. In addition, only 71% of the patients were selected by MRI with a stroke volume evaluation, which is certainly a limit for optimal patient selection [22, 23]. …”
Section: Discussionmentioning
confidence: 99%